Differences in body sway can be identified in Huntington's disease using a practical balance assessment device. (October 2022) - Mustafa, Andrea I.; Corey-Bloom, Jody; Howell, Stephen; Gilbert, Paul E.; Goble, Daniel J.
Abstract: Introduction: Huntington's disease (HD) is a progressive neurodegenerative disorder with motor, cognitive, and psychiatric symptoms that typically manifest in middle adulthood. Balance assessments may be useful for predicting disease onset and progression, but studies are limited. We aimed to enhance estimates of HD onset using an inexpensive and practical body sway assessment device [i.e., Wii Balance Board (WBB)]. Methods: We assessed total body sway (TBS) on 64 HD gene carriers [Presymptomatic HD (PsHD; n  = 16); Prodromal HD (ProHD; n  = 16); HD ( n  = 32)] and 21 demographically similar normal controls (NC) employing a WBB and custom-designed laptop software. Participants completed balance test trials that included combinations of eyes open or closed while standing on a stable versus unstable surface. Non-parametric analyses were conducted to assess group differences in TBS conditions. Results: The HD group had significantly higher TBS in most balance conditions relative to NC, PsHD, and ProHD groups ( ps  < .05). Importantly, the ProHD group demonstrated higher TBS relative to NC in all balance conditions ( ps  < .05) with medium to large effect size ranges ( r ≥ 0.40). No differences in TBS were exhibited between NC and PsHD groups ( ps  > .05). Conclusions: Increased body sway, easily evaluated using a brief, objective balance assessment, may serve as an important functional marker in patients with, and during the transition to, HD. Further studies are needed to confirm and extend these findings. Highlights: Balance assessment in HD, measured by the Wii balance board, may be useful for predicting disease onset and progression. HD subjects had significantly higher total body sway in most balance conditions. Even prodromal HD subjects demonstrated enhanced body sway relative to normal controls. Increased body sway may serve as an important functional marker in the transition to HD.